A preparation process of anti-aging stable ceramic PTC material
By using barium carbonate, trilead tetraoxide, yttrium oxide, lanthanum oxide and other materials in PTC thermistor materials, the sintering process of modified carbon nanotubes and polyvinyl alcohol binders, the solution is solved The aging problem of PTC thermistor material improves the aging resistance and stability of the material, and reduces resistance aging rate and performance fluctuations.
Patent Information
- Application Number
- CN202411281515.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-13
AI Technical Summary
PTC thermistor materials have aging problems during long-term use, resulting in resistance value drift, affecting their anti-aging performance, and increasing the temperature coefficient will increase the risk of voltage breakdown, making it difficult for the existing technology to effectively adjust the temperature coefficient and lift-resistance ratio.
Using a preparation process, by grinding and pre-insulating materials such as barium carbonate, trilead tetraoxide, yttrium oxide, lanthanum oxide and titanium dioxide, combining modified carbon nanotubes and polyvinyl alcohol binders, through different temperature segments The sintering process forms a stable ceramic PTC material, reduces performance fluctuations caused by oxygen vacancies and phase transitions, and improves the density and thermal stability of the material.
It significantly improves the aging resistance and stability of ceramic PTC materials, reduces resistance aging rate, reduces performance degradation, enhances the overall thermal stability and mechanical properties of the material, and avoids performance degradation caused by oxygen deficiency.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PTC thermistor materials and relates to a preparation process of an anti-aging stable ceramic PTC material. Background Art
[0002] The most notable characteristic of PTC thermistors is that their resistance increases dramatically as temperature rises. This characteristic makes PTC thermistors ideal for temperature control components. In heating elements, when the temperature reaches the set value, the PTC resistance increases rapidly, limiting the current flow and reducing the heating power, thereby maintaining the temperature at a stable level. This self-limiting temperature characteristic avoids overheating and damage, and improves the safety of the equipment.
[0003] After a long period of operation, the resistance value of the PTC thermistor will drift to a certain extent. This is the aging problem of the PTC thermistor. The composition of the PTC thermistor ceramic material, the density of the material, and the reaction with some substances in the air will affect the anti-aging performance of the PTC thermistor ceramic material, thereby affecting the normal use of the PTC thermistor ceramic material.
[0004] Generally speaking, increasing the temperature coefficient can reduce the resistance aging rate, but the increase in temperature coefficient will deepen the change of NTC in the front section of the resistance-temperature curve, making the PTC component have the risk of voltage breakdown. Therefore, effectively and controllably adjusting the temperature coefficient and the size of the resistance-rise ratio is an urgent problem to be solved in the current ceramic PTC technology.
[0005] Therefore, it is necessary to develop a preparation process for an anti-aging stable ceramic PTC material to alleviate the deficiencies in the prior art. Summary of the invention
[0006] The object of the present invention is to provide a preparation process of an anti-aging stable ceramic PTC material. The ceramic PTC thermistor material prepared by the present invention has excellent anti-aging properties and stability.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A preparation process of an anti-aging stable ceramic PTC material comprises the following steps:
[0009] S1. Preparation of main raw materials:
[0010] In parts by mass, 50-65 parts of barium carbonate, 12-14 parts of lead tetroxide, 0.2-0.3 parts of yttrium oxide, 0.2-0.3 parts of lanthanum oxide and 25-35 parts of titanium dioxide are stirred to be uniformly mixed, and water is used as a grinding medium to perform ball milling at a speed of 400-500 r / min for 6-8 hours. After the ball milling, the mixture is dried at 100° C. for 7 hours, and then kept at 750-870° C. for 5 hours to obtain the main raw material;
[0011] S2. Prepare ingredients:
[0012] In parts by mass, 70-80 parts of a main raw material, 2-4 parts of a dopant, and 3-5 parts of a sintering aid are sequentially added into a ball mill, and then 100-130 parts of water and 150-200 parts of ball mill beads with a particle size of 5-10 mm are added. The ball milling time is 18-21 hours. After the wet ball milling is completed, the ingredients are dried at 100° C. for 7 hours, and then reacted at a temperature of 1070-1160° C. for 2-3 hours to prepare the ingredients;
[0013] S3, preparing green sheets:
[0014] 8-10 parts by weight of a modified binder are added to the ingredients, and the green sheets are formed by spray granulation and static pressure treatment for 150-250 seconds at a temperature of 50-70° C. and a pressure of 20-30 MPa, wherein the modified binder is a mixed solution obtained by fully mixing 3-5 parts of polyvinyl alcohol, 2-4 parts of fatty alcohol polyoxyethylene ether, 3-5 parts of modified carbon nanotubes and 93-97 parts of ethanol;
[0015] S4, sintering:
[0016] S41, debinding: heating the green sheet in a tube furnace at a heating rate of 4°C / min to 700°C and keeping the temperature for 0.5-1h;
[0017] S42, synthesis: keep the heating rate constant, raise the temperature to 1200°C, and keep it for 0.5~1h;
[0018] S43, high temperature sintering: in a nitrogen atmosphere, adjust the heating rate to 10-12°C / min, raise the temperature to 1250-1300°C, and sinter at high temperature for 0.5-1.5h;
[0019] S44, full oxidation: cool down from 1250~1300℃ at a cooling rate of 5~7℃ / min to 1050℃ and keep it for 0.5~1h, then cool down naturally to room temperature to complete the sintering of the green sheet;
[0020] S5. After grinding and polishing, the anti-aging stable ceramic PTC material is obtained.
[0021] As a preferred technical solution of the present invention, in step S2, the dopant is one of zinc oxide and manganese dioxide.
[0022] As a preferred technical solution of the present invention, in step S2, the sintering aid is one or more of alumina, silicon dioxide and boron nitride.
[0023] As a preferred technical solution of the present invention, in step S3, the modified carbon nanotubes are prepared by:
[0024] The carbon nanotubes are treated by soaking in a sulfuric acid solution with a mass fraction of 15% for 2 hours, and then the nanotubes obtained after acid treatment are washed and dried, and then soaked in a mixed salt solution with a mass fraction of 20-30% for 3-5 hours. After sensitization treatment, the modified carbon nanotubes are prepared, wherein the mixed salt is tin sulfate and palladium chloride with a mass ratio of 1:1.
[0025] As a preferred technical solution of the present invention, in step S2 and step S4, the heat preservation and sintering processes are both carried out in a closed environment.
[0026] In the present invention, the main raw materials are prepared by grinding barium carbonate, lead tetroxide, yttrium oxide, lanthanum oxide and titanium dioxide and pre-heating at high temperature, and barium titanate is prepared by a solid phase method. Yttrium oxide is used as a donor, and its introduction will produce barium vacancies, which will inhibit the generation of oxygen vacancies. The more donors are introduced, the more barium vacancies there are, thereby weakening the oxygen vacancy diffusion mechanism. In addition, due to La 3+ and Y 3+ The ionic radius is smaller than that of Ba 2+ , so when La 3+ and Y 3+ Replace Ba 2+ When the crystal distance of barium titanate is reduced, the grain size is reduced. As rare earth oxides, the doping of yttrium oxide and lanthanum oxide improves the dielectric properties of the material by affecting the crystal structure of barium titanate, thereby making the performance of the PTC resistor material more stable at different temperatures. In the present invention, yttrium oxide and lanthanum oxide are used as sintering aids to reduce the sintering temperature and sintering behavior of ceramic materials, reduce defects and stress concentration during the sintering process, and improve the density and uniformity of ceramic PTC materials.
[0027] Barium titanate has ferroelectricity and will undergo phase transition near the Curie temperature, resulting in a sharp change in resistivity. The doping of yttrium oxide and lanthanum oxide in the present invention can regulate this phase transition process, making the phase transition more stable, thereby reducing the performance fluctuation caused by the phase transition, thereby improving the stability of the barium titanate thermistor at high temperatures. The addition of yttrium oxide and lanthanum oxide can reduce the mobility of oxygen in barium titanate, thereby reducing the diffusion and escape of oxygen at high temperatures, which helps to maintain the chemical stability and thermal stability of the material and prevent performance degradation caused by oxygen deficiency. At the same time, as rare earth metals, rare earth elements can form more stable chemical bonds with elements in barium titanate, making it less likely to decompose at high temperatures, thereby improving the overall thermal stability of the material. At the same time, the doping of rare earth elements can inhibit the aging reaction of barium titanate at high temperatures and improve aging resistance.
[0028] At the same time, lead tetroxide is added to the main raw material. Lead tetroxide can not only change the Curie temperature, but also have a synergistic effect with barium titanate to change the microstructure (grain size, grain boundary state) of barium titanate-based materials, further enhance the PTC effect of the material, and improve the mechanical properties of barium titanate-based materials. Improve the durability of ceramic PTC materials. Since lead tetroxide is easy to volatilize near 900°C, sealing treatment is carried out during the firing process to inhibit the volatilization of lead tetroxide.
[0029] In the present invention, the modified binder is prepared by compounding modified carbon nanotubes, polyvinyl alcohol and fatty alcohol polyoxyethylene ether. The viscosity of polyvinyl alcohol is good, but the adhesion of polyvinyl alcohol is greatly affected by temperature. Therefore, adding surfactant fatty alcohol polyoxyethylene ether to polyvinyl alcohol can improve the interface interaction between polyvinyl alcohol and the bonded material, improve the permeability of polyvinyl alcohol between the main raw material, sintering aid and dopant surface, increase the attraction and mechanical bite between molecules, thereby improving the bonding strength. In addition, the ether bond of fatty alcohol polyoxyethylene ether is more stable and not easy to be destroyed, thereby improving the bonding strength. High durability of polyvinyl alcohol binder; at the same time, by treating carbon nanotubes with acid, introducing hydroxyl groups on the surface, and then sensitizing with salt solution, a thin layer of catalytic metal can be attached to the surface. When the modified carbon nanotubes are mixed with polyvinyl alcohol and fatty alcohol polyoxyethylene ether, the three can form intermolecular hydrogen bonds through the hydroxyl groups on the surface of the carbon nanotubes, thereby enhancing the binding force between the three and avoiding the agglomeration of the carbon nanotubes, thereby forming a network-like structure; and because the carbon nanotubes have also been sensitized, they can help thermistor materials reduce local resistance fluctuations and form a more stable conductive network.
[0030] In the present invention, the ceramic thermistor material is fully sintered by adjusting different temperature sections. First, the temperature is raised to 1160° C. and kept for 0.5-1 hour, which can promote the initial densification of the PTC thermistor material, thereby reducing the pores and defects in the material, allowing the material to adapt to the high temperature environment and avoid stress and defects. Then, high-temperature sintering is performed at 1250-1300° C. to reduce the uncertainty in the sintering process, thereby achieving material densification, grain growth and rearrangement. Finally, sufficient oxidation is performed, and the temperature is lowered from 1250-1300° C. to 1100° C. at a lower cooling rate and kept for 0.5-1 hour to reduce stress. In addition, sufficient oxygen is supplemented through sintering, which can promote the conversion of unstable phases or defects formed during the high-temperature sintering process into a more stable form, thereby improving the overall stability and aging resistance of the material.
[0031] Beneficial effects of the present invention:
[0032] In the present invention, the main raw materials prepared by grinding and high-temperature pre-insulation of barium carbonate, lead tetroxide, yttrium oxide, lanthanum oxide and titanium dioxide by a solid phase method are granulated and formed with a dopant and a sintering aid under the bonding of a modified polyvinyl alcohol binder, and the stability and aging resistance of the material are fully improved by gradual sintering at different temperature stages. DETAILED DESCRIPTION
[0033] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0034] In the following examples and comparative examples:
[0035] In step S2 and step S4, the heat preservation and sintering processes are carried out in a closed environment;
[0036] Barium carbonate: purchased from Wuhan Jiyesheng Chemical Co., Ltd., purity: 99%;
[0037] Lead tetroxide: purchased from Wuhan Jiyesheng Chemical Co., Ltd.
[0038] Yttrium oxide: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: Y835830;
[0039] Lanthanum oxide: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: L812319:
[0040] Titanium dioxide: purchased from Kangdisi Chemical (Hubei) Co., Ltd., product number: 186412;
[0041] Manganese dioxide: purchased from Shanghai Kaisai Chemical Co., Ltd., product number: 1313-13-9;
[0042] Alumina: purchased from Kangdisi Chemical (Hubei) Co., Ltd.;
[0043] Zinc oxide: purchased from Wuhan Jiyesheng Chemical Co., Ltd.
[0044] Silica: purchased from Wuhan Jixinyibang Biotechnology Co., Ltd.;
[0045] Carbon nanotubes: purchased from Hubei Guangao Biotechnology Co., Ltd.
[0046] Tin sulfate: purchased from Beijing Bailingwei Technology Co., Ltd., product number: 372891;
[0047] Palladium chloride: purchased from Hubei Wanye Zhongcheng Chemical Reagent Co., Ltd.;
[0048] Polyvinyl alcohol: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: P875285;
[0049] Fatty alcohol polyoxyethylene ether: purchased from Shandong Xinheng Chemical Co., Ltd.
[0050] Example 1
[0051] S1. Preparation of main raw materials:
[0052] In parts by mass, 50 parts of barium carbonate, 12 parts of lead tetroxide, 0.2 parts of yttrium oxide, 0.2 parts of lanthanum oxide and 25 parts of titanium dioxide were stirred and mixed uniformly, and ball-milled at a speed of 400 r / min for 8 hours with water as a grinding medium. After the ball-milling, the mixture was dried at 100° C. for 7 hours, and then kept at 750° C. for 5 hours to obtain the main raw material;
[0053] S2. Prepare ingredients:
[0054] In parts by mass, 70 parts of the main raw material, 2 parts of manganese dioxide, and 3 parts of aluminum oxide are added to a ball mill in sequence, and then 100 parts of water and 150 parts of ball mill beads with a particle size of 5 mm are added. The ball milling time is 18 hours. After the wet ball milling is completed, the ingredients are dried at 100° C. for 7 hours, and then reacted at a temperature of 1070° C. for 3 hours to prepare the ingredients;
[0055] S3, preparing green sheets:
[0056] In parts by mass, the carbon nanotubes are treated by soaking in a sulfuric acid solution with a mass fraction of 15% for 2 hours, and then the nanotubes obtained by the acid treatment are washed and dried, and then soaked in a mixed salt solution with a mass fraction of 20% for 5 hours. After sensitization treatment, modified carbon nanotubes are prepared, wherein the mixed salt is tin sulfate and palladium chloride with a mass ratio of 1:1;
[0057] 8 parts of modified binder are added to the ingredients, and the mixture is granulated by spraying, and statically pressed for 150 seconds at a temperature of 50° C. and a pressure of 20 MPa to form a green sheet, wherein the modified binder is a mixed solution obtained by fully mixing 3 parts of polyvinyl alcohol, 2 parts of fatty alcohol polyoxyethylene ether, 3 parts of modified carbon nanotubes and 93 parts of ethanol;
[0058] S4, sintering:
[0059] S41, debinding: heating the green sheet in a tube furnace at a heating rate of 4°C / min to 700°C and keeping the temperature for 0.5h;
[0060] S42, synthesis: keep the heating rate unchanged, raise the temperature to 1200°C, and keep it for 0.5h;
[0061] S43, high temperature sintering: in a nitrogen atmosphere, the heating rate is adjusted to 10°C / min, the temperature is raised to 1250°C, and the high temperature sintering and heat preservation reaction is carried out for 0.5h;
[0062] S44, full oxidation: cooling from 1250°C to 1050°C at a cooling rate of 5°C / min, keeping the temperature for 0.5h, and then cooling naturally to room temperature to complete the sintering of the green sheet;
[0063] S5. After grinding and polishing, the anti-aging stable ceramic PTC material is obtained.
[0064] Example 2
[0065] S1. Preparation of main raw materials:
[0066] In parts by mass, 58 parts of barium carbonate, 13 parts of lead tetroxide, 0.25 parts of yttrium oxide, 0.25 parts of lanthanum oxide and 30 parts of titanium dioxide were stirred and mixed uniformly, and ball-milled at a speed of 450 r / min for 7 hours with water as a grinding medium. After the ball-milling, the mixture was dried at 100° C. for 7 hours, and then kept at 810° C. for 5 hours to obtain the main raw material;
[0067] S2. Prepare ingredients:
[0068] In parts by mass, 75 parts of the main raw material, 3 parts of manganese dioxide, and 45 parts of aluminum oxide are added to a ball mill in sequence, and then 120 parts of water and 170 parts of ball mill beads with a particle size of 8 mm are added. The ball milling time is 19 hours. After the wet ball milling is completed, the ingredients are dried at 100° C. for 7 hours, and then reacted at a temperature of 1010° C. for 2.5 hours to prepare the ingredients;
[0069] S3, preparing green sheets:
[0070] In parts by mass, the carbon nanotubes are treated by soaking in a sulfuric acid solution with a mass fraction of 15% for 2 hours, and then the nanotubes obtained by the acid treatment are washed and dried, and then soaked in a mixed salt solution with a mass fraction of 25% for 4 hours. After sensitization treatment, modified carbon nanotubes are prepared, wherein the mixed salt is tin sulfate and palladium chloride with a mass ratio of 1:1;
[0071] 9 parts of modified binder are added to the ingredients, and the mixture is granulated by spraying, and statically pressed for 200 seconds at a temperature of 60° C. and a pressure of 25 MPa to form a green sheet, wherein the modified binder is a mixed solution obtained by fully mixing 4 parts of polyvinyl alcohol, 3 parts of fatty alcohol polyoxyethylene ether, 4 parts of modified carbon nanotubes and 95 parts of ethanol;
[0072] S4, sintering:
[0073] S41, debinding: heating the green sheet in a tube furnace at a heating rate of 4°C / min to 700°C and keeping the temperature for 0.8h;
[0074] S42, synthesis: keep the heating rate unchanged, raise the temperature to 1200°C, and keep it for 0.8h;
[0075] S43, high temperature sintering: in a nitrogen atmosphere, the heating rate is adjusted to 11°C / min, the temperature is raised to 1280°C, and the high temperature sintering is carried out for 1 hour;
[0076] S44, full oxidation: cooling from 1280°C to 1050°C at a cooling rate of 6°C / min, keeping the temperature for 0.8h, and then cooling naturally to room temperature to complete the sintering of the green sheet;
[0077] S5. After grinding and polishing, the anti-aging stable ceramic PTC material is obtained.
[0078] Example 3
[0079] S1. Preparation of main raw materials:
[0080] In parts by mass, 65 parts of barium carbonate, 14 parts of lead tetroxide, 0.3 parts of yttrium oxide, 0.3 parts of lanthanum oxide and 35 parts of titanium dioxide are stirred to be uniformly mixed, and ball milled at a speed of 500 r / min for 6 hours with water as a grinding medium, and dried at 100° C. for 7 hours after ball milling, and then kept warm at 870° C. for 5 hours to obtain the main raw material;
[0081] S2. Prepare ingredients:
[0082] In parts by mass, 80 parts of the main raw material, 4 parts of zinc oxide, and 5 parts of silicon dioxide are added to a ball mill in sequence, and then 130 parts of water and 200 parts of ball mill beads with a particle size of 10 mm are added. The ball milling time is 21 hours. After the wet ball milling is completed, the ingredients are dried at 100° C. for 7 hours, and then reacted at a temperature of 1160° C. for 3 hours to prepare the ingredients;
[0083] S3, preparing green sheets:
[0084] In parts by mass, the carbon nanotubes were treated by soaking in a sulfuric acid solution with a mass fraction of 15% for 2 hours, and then the nanotubes obtained by the acid treatment were washed and dried, and then soaked in a mixed salt solution with a mass fraction of 30% for 5 hours. After sensitization treatment, modified carbon nanotubes were prepared, wherein the mixed salt was tin sulfate and palladium chloride with a mass ratio of 1:1;
[0085] 10 parts of modified binder are added to the ingredients, and the mixture is granulated by spraying, and statically pressed for 250 seconds at a temperature of 70° C. and a pressure of 30 MPa to form a green sheet, wherein the modified binder is a mixed solution obtained by fully mixing 5 parts of polyvinyl alcohol, 4 parts of fatty alcohol polyoxyethylene ether, 5 parts of modified carbon nanotubes and 97 parts of ethanol;
[0086] S4, sintering:
[0087] S41, debinding: heating the green sheet in a tube furnace at a heating rate of 4°C / min to 700°C and keeping the temperature for 1h;
[0088] S42, synthesis: keep the heating rate unchanged, raise the temperature to 1200°C, and keep it for 1h;
[0089] S43, high temperature sintering: in a nitrogen atmosphere, the heating rate is adjusted to 12°C / min, the temperature is raised to 1300°C, and the high temperature sintering and heat preservation reaction is carried out for 1.5 hours;
[0090] S44, full oxidation: cooling from 1300°C to 1050°C at a cooling rate of 7°C / min and keeping the temperature for 1 hour, then cooling naturally to room temperature to complete the sintering of the green sheet;
[0091] S5. After grinding and polishing, the anti-aging stable ceramic PTC material is obtained.
[0092] Comparative Example 1
[0093] The difference between Comparative Example 1 and Example 1 is that yttrium oxide is not added in step S1 of Comparative Example 1, and the other operations are the same.
[0094] Comparative Example 2
[0095] The difference between Comparative Example 2 and Example 1 is that in step S1 of Comparative Example 2, lanthanum oxide is not added, and the other operations are the same.
[0096] Comparative Example 3
[0097] The difference between Comparative Example 3 and Example 1 is that in step S1 of Comparative Example 3, lead tetroxide is not added, and the other operations are the same.
[0098] Comparative Example 4
[0099] The difference between Comparative Example 4 and Example 1 is that the carbon nanotubes in Comparative Example 4 are not modified, and the other operations are the same.
[0100] Comparative Example 5
[0101] The difference between Comparative Example 5 and Example 1 is that fatty alcohol polyoxyethylene ether is not added in Comparative Example 5, and the other operations are the same.
[0102] Comparative Example 6
[0103] The difference between Comparative Example 6 and Example 1 is that no carbon nanotubes are added in Comparative Example 6, and the other operations are the same.
[0104] Comparative Example 7
[0105] The difference between Comparative Example 7 and Example 1 is that step S42 is not performed in Comparative Example 7, and the remaining operations are the same.
[0106] Comparative Example 8
[0107] The difference between Comparative Example 8 and Example 1 is that the S44 operation is not performed in Comparative Example 8, and the other operations are the same.
[0108] The resistor materials prepared in the examples and comparative examples were ground to 24 mm x 15 mm x 2.42 mm, chamfered, cleaned and dried, and aluminum electrodes were sprayed on both sides to prepare finished products. The performance was tested:
[0109] 1. 10,000-times on-off aging data: Under normal environmental conditions, the PTC component is powered on (no wind) for 1 minute and powered off (air cooling) for 1 minute under a 120VAC test voltage, which is a cycle for 10,000 times. The data obtained are shown in Table 1:
[0110] Table 1
[0111]
[0112] According to the results in Table 1, after 1000 times of anti-aging tests, the resistivity change of the resistor material prepared in the embodiment is smaller than that of the comparative example, so the resistor material prepared in the embodiment has better anti-aging performance.
[0113] 2. Stability test:
[0114] The prepared resistor material was placed in a 100° C. thermostat for a thermal stability test. After 2 hours, the resistor material was taken out and the resistance value was remeasured to see if there was any change. The results showed that the resistance values of Examples 1-3 did not change, while the resistance values of Comparative Examples 1-8 changed, indicating that the thermistor material prepared by the present invention has better stability.
[0115] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A preparation process of an anti-aging stable ceramic PTC material, characterized in that: The following steps are involved: S1. Preparation of main raw materials: In parts by mass, 50-65 parts of barium carbonate, 12-14 parts of lead tetroxide, 0.2-0.3 parts of yttrium oxide, 0.2-0.3 parts of lanthanum oxide and 25-35 parts of titanium dioxide are stirred to be uniformly mixed, and water is used as a grinding medium to perform ball milling at a speed of 400-500 r / min for 6-8 hours. After the ball milling, the mixture is dried at 100° C. for 7 hours, and then kept at 750-870° C. for 5 hours to obtain the main raw material; S2. Prepare ingredients: In parts by mass, 70-80 parts of a main raw material, 2-4 parts of a dopant, and 3-5 parts of a sintering aid are sequentially added into a ball mill, and then 100-130 parts of water and 150-200 parts of ball mill beads with a particle size of 5-10 mm are added. The ball milling time is 18-21 hours. After the wet ball milling is completed, the ingredients are dried at 100° C. for 7 hours, and then reacted at a temperature of 1070-1160° C. for 2-3 hours to prepare the ingredients; S3, preparing green sheets: 8-10 parts by weight of a modified binder are added to the ingredients, and the green sheets are formed by spray granulation and static pressure treatment at a temperature of 50-70° C. and a pressure of 20-30 MPa for 150-250 seconds, wherein the modified binder is a mixed solution obtained by fully mixing 3-5 parts by weight of polyvinyl alcohol, 2-4 parts of fatty alcohol polyoxyethylene ether, 3-5 parts of modified carbon nanotubes and 93-97 parts of ethanol; S4, sintering: S41, debinding: heating the green sheet in a tube furnace at a heating rate of 4°C / min to 700°C and keeping the temperature for 0.5-1h; S42, synthesis: keep the heating rate constant, raise the temperature to 1200°C, and keep it for 0.5~1h; S43, high temperature sintering: in a nitrogen atmosphere, adjust the heating rate to 10-12°C / min, raise the temperature to 1250-1300°C, and sinter at high temperature for 0.5-1.5h; S44, full oxidation: cool down from 1250~1300℃ at a cooling rate of 5~7℃ / min to 1050℃ and keep it for 0.5~1h, then cool down naturally to room temperature to complete the sintering of the green sheet; S5. After grinding and polishing, the anti-aging stable ceramic PTC material is obtained.
2. The preparation process of the anti-aging stable ceramic PTC material according to claim 1, characterized in that: In step S2, the dopant is one of zinc oxide and manganese dioxide.
3. The preparation process of the anti-aging stable ceramic PTC material according to claim 1, characterized in that: In step S2, the sintering aid is one or more of alumina, silicon dioxide and boron nitride.
4. The preparation process of the anti-aging stable ceramic PTC material according to claim 1, characterized in that: In step S3, the modified carbon nanotubes are prepared by: The carbon nanotubes are treated by soaking in a sulfuric acid solution with a mass fraction of 15% for 2 hours, and then the nanotubes obtained after acid treatment are washed and dried, and then soaked in a mixed salt solution with a mass fraction of 20-30% for 3-5 hours. After sensitization treatment, the modified carbon nanotubes are prepared, wherein the mixed salt is tin sulfate and palladium chloride with a mass ratio of 1:
1.
5. The preparation process of the anti-aging stable ceramic PTC material according to claim 1, characterized in that: In step S2 and step S4, the heat preservation and sintering processes are all carried out in a closed environment.
Citation Information
Patent Citations
Modified barium titanate foamed ceramic / thermosetting resin composite material and preparation method thereof
CN105419328A
High heat-conduction ceramic heat-radiation nanocomposite material used for LED lamp
CN107434414A